KINETIKA ADSORPSI AMMONIUM DARI KOPOLIMER SELULOSA JERAMI PADI DENGAN ASAM AKRILAT DAN AKRILAMIDA - Wina Yulianti (Jurnal Biofisika, 2012)
Copolymerization of cellulose from rice straw with acrylic acid and acrylamide produce biodegradable superabsorbent Copolymerization was carried out at 65 C under nitrogen athmosphere. Initiator and cross linking agent used were potassium peroxodisulfate and N'N-methylene bis acrylamide. Superabsorbent produced is anionic, that can bind ammonium cation. The kinetics of swelling adsorption was following pseudo second-order equation.